Answer
e^c = 3
Step by step explanation
The general exponential equation is y = a^x, where "a" is the base and "x" is the exponent.
We are given c = ln 3
Here the base is "e"
e^c = e^ln 3
e^c = 3 [base "e" and "ln" get cancelled because they are inverse]
Therefore, the answer is e^c = 3
Hope you will understand the concept.
Thank you.
Answer:
e^c = 3
Step-by-step explanation:
A.P.E.X.
y = -2x-2
Answer:
x = 109
Step-by-step explanation:
The slope-intercept form is
y = mx + b,
where m = slope, and b = y-intercept
Now we get the y-intercept and the slope from the graph.
The y-intercept, b, is 4.
To find the slope, start at (-2, 0). Go up 4 and right 2 to point (0, 2). That is a rise of 4 and a run of 2.
m = slope = rise/run = 4/2 = 2
Equation:
y = mx + b
y = 2x + 4
Answer: y = 2x + 4
x = y + 5
A.
x + y = y + 5
B.
x + (y + 5) = 6
C.
x = (x – 6) + 5
D.
(y + 5) + y = 6